Development and Assessment of “Chem this Vlab” Learning Package - Alvin Larida (Journal of Science and Science Education, 2021)
This study determined the difficulty level of answering Chemistry problems of the STEM students of Libertad National High School. The respondents of the study were seventy-three (73) purposely selected students for the school year 2020-2021. Thereafter, the researcher developed a Learning Package in Chemistry to augment the learning in the new normal. It will be known as Chem in this VLab Learning Activities that focus on Chemical Solutions, Thermodynamics, and Chemical Kinetics. To validate the quality of the learning package, selected experts assessed the tool on three components: content, technical, and instructional qualities. The results revealed that students had poor performance in answering Chemistry problems and find Chemistry as difficult subject to learn. Therefore, learning activities are developed to aid their understanding on the selected topics. The instructional material was rated as a good instructional tool in learning Chemistry by the experts and recommended to be utilized in the online distance learning modality.